PHARMACOLOGICAL APPLICATIONS OF CONTROLLED RELEASE DRUGS - Melo, Vinicius Farias de; Coelho, José Leonardo Gomes; Sousa, Carmelita Maria Silva; Fernandes, Elis Augusta Moura Dias; Brito, Rivaniery Teles Braga Emídio de; Santana, Willma José de (Amadeus International Multidisciplinary Journal, 2020)
Abstract: This present aims to discuss the main systems of controlled release of drugs and their pharmacological applications. For this purpose, this study was based on articles between the years 2016 to 2020 in English, Spanish and Portuguese, using the following descriptors: Pharmacological applications, Controlled release, Conventional release. The main systems discussed were polymeric nanoparticles, liposomes and cyclodextrins. These systems guarantee a constant concentration of the drug in the sage and promote a dose comfort to the patient, minimizing the amount of administration, unexpected effects. Keywords: Pharmacological applications, Controlled release, Conventional release.